2021
DOI: 10.3390/brainsci11121622
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrolysin Prevents Brain Injury in a Mouse Model of Liver Damage

Abstract: Liver damage can lead to secondary organ damage by toxic substances and catabolic products accumulation which can increase the permeability of blood-brain barrier, leading to cognitive impairment. The only real treatment for end stage liver failure is grafting. With some, but not all, neurological symptoms subsiding after transplantation, the presence of brain damage can impair both the short and long-term outcome. We tested if Cerebrolysin can prevent brain injury in an experimental model of non-viral liver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…While depressive-like behavior was reported in models of chronic liver injury caused by intraperitoneal injection of CCl 4 and D-galactosamine ( Zhu et al, 2020 ), in the present study we were not able to show a similar trend in MCD-fed animals without any depressive-like behavior inducing protocols. This could mean that alterations in behavior resulting from liver damage may be contingent upon the degree of liver damage, as the use of intraperitoneal injection of CCl 4 induces necrosis, swelling, loose cytoplasm and inflammatory infiltrate, D-galactosamine was reported to induce scattered inflammatory infiltration and hepatic sinusoid hyperemia ( Zhu et al, 2020 ), and MCD induces steatosis with intra-lobar diffuse inflammation ( Morega et al, 2021 ). Except for some minor behavioral differences, most of the studies do not report the sex of C57BL/6 mice as a determining factor for varied outcomes following liver injury ( Zhu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While depressive-like behavior was reported in models of chronic liver injury caused by intraperitoneal injection of CCl 4 and D-galactosamine ( Zhu et al, 2020 ), in the present study we were not able to show a similar trend in MCD-fed animals without any depressive-like behavior inducing protocols. This could mean that alterations in behavior resulting from liver damage may be contingent upon the degree of liver damage, as the use of intraperitoneal injection of CCl 4 induces necrosis, swelling, loose cytoplasm and inflammatory infiltrate, D-galactosamine was reported to induce scattered inflammatory infiltration and hepatic sinusoid hyperemia ( Zhu et al, 2020 ), and MCD induces steatosis with intra-lobar diffuse inflammation ( Morega et al, 2021 ). Except for some minor behavioral differences, most of the studies do not report the sex of C57BL/6 mice as a determining factor for varied outcomes following liver injury ( Zhu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…OFT was performed as previously described ( Morega et al, 2021 ). Briefly, the test was carried out in an open arena [50 cm (length) × 33 cm (width) × 15 cm (height)]; the mice were placed individually in the center of the box, and the behavioral variables were recorded for 10 min and then analyzed (EthoVision XT 17, Noldus Technology).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In older mice, the proliferation might be an indirect consequence of age‐induced dysfunction of the blood‐brain barrier (BBB) 47 . We know now that BBB changes associated with aged can have also pathological causes such as infections, 48 lifestyle 49,50 or even neurodegenerative pathologies 51 . Regardless of the cause of BBB disruption in the aged cortex, there is an imbalance of molecular transport from the parenchyma to the blood, creating a pro‐inflammatory environment that highlights the need of an increase of microglia density.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that animal studies have identified several strategies for stroke improvement, there is a lack of translation from preclinical to clinical trials. Although several attempts have been made to investigate the efficacy of behavior testing in animal models of white matter injury [ 73 ] and rodent models of stroke [ 74 ], some even measuring the validity and reliability of neurological scores in mice [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ], all have generated conflicting results.…”
Section: Discussionmentioning
confidence: 99%